2020
DOI: 10.3390/molecules25184043
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Catalytic Activity, and DFT Calculations of Zn(II) Hydrazone Complexes

Abstract: Two new Zn(II) complexes with tridentate hydrazone-based ligands (condensation products of 2-acetylthiazole) were synthesized and characterized by infrared (IR) and nuclear magnetic resonance (NMR) spectroscopy and single crystal X-ray diffraction methods. The complexes 1, 2 and recently synthesized [ZnL3(NCS)2] (L3 = (E)-N,N,N-trimethyl-2-oxo-2-(2-(1-(pyridin-2-yl)ethylidene)hydrazinyl)ethan-1-aminium) complex 3 were tested as potential catalysts for the ketone-amine-alkyne (KA2) coupling reaction. The gas-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…These structures are called soft molecules. 34 In this study, ΔE values are listed as 9> 8> 7> 6. As a result, it can be said that molecule 6 can show good corrosion inhibitor performance (Table II).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These structures are called soft molecules. 34 In this study, ΔE values are listed as 9> 8> 7> 6. As a result, it can be said that molecule 6 can show good corrosion inhibitor performance (Table II).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Investigation of various arylnitrones (Scheme 6), concluded that either electron-withdrawing or electron-donating groups on various positions of the phenyl-imino moieties yielded the desired quinolines in high yields (67)(68)(69)(70)(71). Derivatives bearing groups of either electron-withdrawing or -donating ability at either the paraor the metaposition of the phenyl ring bearing the N-O group gave the corresponding products in approximately 80% yield (72)(73)(74)(75). Attempts with heterocyclicsubstituted nitrones failed, most probably owing to the strong metal-heteroatom coordination.…”
Section: Transformations With N-oxide As Tdgmentioning
confidence: 99%
“…All aforementioned aspects of sustainable transition metal-catalyzed C-H activation reactions constitute important weapons in the arsenal of contemporary organic chemistry. In this article, enabled by our ongoing interest in the area of sustainable catalysis [40,[68][69][70][71][72][73][74][75][76], we review and critically examine the use of traceless directing groups (TDG) in sustainable metal catalyzed C-H activation, highlighting the versatility provided by these categories of DGs coupled with earth-abundant, sustainable metals. In line with our previous work [40], we examine the advancements regarding the use of TDGs in transformations catalyzed by complexes of the most abundant, least toxic and biocompatible 3d metals.…”
Section: Introductionmentioning
confidence: 99%
“…A class of heterocyclic azo dyes is the thiazolylazo dye. Thiazoles are an important class of heterocyclic compounds which are related with many types of biological properties, probably by virtue of the -N=C-S− group, these include insecticidal, herbicidal, anti-oxidant, -bacterial, -convulsant and -inflammatory [29] [30] [31] [32] [33]. Thiazoles are readily capable of crossing cellular membranes owing to their better liposolubility, attributed to the presence of a sulphur atom [32].…”
Section: Introductionmentioning
confidence: 99%